Information technologies in energy planning of cities and towns - Grigonis, Vytautas; Burinskienė, Marija (Journal of Civil Engineering and Management, 2002)
It is commonly accepted that sustainable development covers economic, social and ecological aspects and maintains vital exchange process between socioeconomic systems and natural environment. Interdisciplinary subjects emerge as a particular result of sustainable development. Energy planning is one of them. In the past inadequate technologies and inaccessible data limited many research activities. At present great progress is achieved in the fields mentioned above. The cheapest and most precise source of data the is recent register of real estate. Therefore it is possible to design a database for energy planning, where classification criteria could be selected and data could be summarized and structured according to these criteria. The possibilities to use these data would be provided in particular models. Using data processing programs could do it. Some examples are given how databases are used in energy planning and some suggestions how make necessary changes are presented in the article. It is also mentioned what kind of extra data are required to have a multidimensional database. Data are related with data processing programs in order to improve and accelerate accumulation of data. This, in turn, helps using data widely for energy planning.Frist Published Online: 30 Jul 2012